2020
DOI: 10.3390/molecules25245959
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Screening of Four Bioactive Citroflavonoids: In Vitro, In Vivo, and In Silico Approaches

Abstract: Many studies describe different pharmacological effects of flavonoids on experimental animals and humans. Nevertheless, few ones are confirming the safety of these compounds for therapeutic purposes. This study aimed to investigate the preclinical safety of naringenin, naringin, hesperidin, and quercetin by in vivo, in vitro, and in silico approaches. For this, an MTT-based cytotoxicity assay in VERO and MDCK cell lines was performed. In addition, acute toxicity was evaluated on Wistar rats by OECD Guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…The results showed that both hesperidin and hesperetin showed no mutagenic effect against frameshift strain TA98. In another study, Ortiz-Andrade et al (2020) assessed the preclinical safety of hesperidin via a combination of in vitro , in vivo and in silico approaches. The MTT assay revealed the lack of cytotoxicity of hesperidin (125–1000 µg/mL) against VERO and MDCK kidney cell lines.…”
Section: Safety Profiles Of Hesperidin and Hesperetinmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that both hesperidin and hesperetin showed no mutagenic effect against frameshift strain TA98. In another study, Ortiz-Andrade et al (2020) assessed the preclinical safety of hesperidin via a combination of in vitro , in vivo and in silico approaches. The MTT assay revealed the lack of cytotoxicity of hesperidin (125–1000 µg/mL) against VERO and MDCK kidney cell lines.…”
Section: Safety Profiles Of Hesperidin and Hesperetinmentioning
confidence: 99%
“…Furthermore, the ACD/Tox Suite® platform was employed to predict the toxicity of hesperidin in terms of its acute toxicity (rodent LD 50 ) as well as its capabilities to block human Ether-à-go-go-Related Gene (hERG) channel or cytochrome P450 (CYP450). The software gave rise to predicted LD 50 values of 1600 mg/kg (intraperitoneal injection) and 3000 mg/kg (oral administration) ( Ortiz-Andrade et al, 2020 ), placing hesperidin in the acute toxicity category IV (i.e., non-toxic) according to the OECD guide 423 ( Organisation for Economic Co-operation and Development, 2001 ). Additionally, therapeutic concentrations of hesperidin were predicted to have 0% probability of inducing hERG blockage that would otherwise cause long QT syndrome and sudden cardiac death, together with very low probabilities of inhibiting CYP450 activities ( Ortiz-Andrade et al, 2020 ).…”
Section: Safety Profiles Of Hesperidin and Hesperetinmentioning
confidence: 99%
“…The NOAEL (no-observed-adverse-effect-level) of naringin is proposed to be greater than 1250 mg/kg/day following daily oral administrations to SD rats for six months (corresponding to 12 g for a 60 kg human) [ 47 ]. The cytotoxicity assay showed that naringin had no toxicity to VERO and MDCK cells at concentrations ranging from 125 to 750 μ g/mL [ 48 ]. Hence, naringin is generally considered to be a relatively harmless or nontoxic substance.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence suggests that they could be classified as low-risk molecular entities, useful substances for drug development. According to results, a mixture of naringenin/hesperidin could be a good candidate for developing a dosage form with antidiabetic and antihypertensive properties [5].…”
Section: Introductionmentioning
confidence: 99%